We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
128
1
avatar

Let P be the intersection point of the line through points D = (1, 1, 2) and E = (2, 3, 4) with the plane through A = (0,1,1), B = (1,1,0) and C = (1,0,3). What is P?

 Aug 5, 2019
 #1
avatar+23295 
+2

Let P be the intersection point of the line through points D = (1, 1, 2) and E = (2, 3, 4) 

with the plane through A = (0,1,1), B = (1,1,0) and C = (1,0,3).

What is P?

 

\(\begin{array}{|rcl|rclrcl|} \hline \text{plane} &&& \text{line} \\ \hline && A = \begin{pmatrix} 0\\ 1\\ 1 \end{pmatrix} \qquad B = \begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix} \qquad C = \begin{pmatrix} 1\\ 0\\ 3 \end{pmatrix} \qquad & && D = \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix} \qquad E = \begin{pmatrix} 2\\ 3\\ 4 \end{pmatrix} \\ \vec{x} &=& \vec{B}+s(\vec{A}-\vec{B})+t(\vec{C}-\vec{B}) & \vec{x} &=& \vec{D}+r(\vec{E}-\vec{D}) \\\\ \vec{x} &=&\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix} +s\left(\begin{pmatrix} 0\\ 1\\ 1 \end{pmatrix}-\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix}\right) +t\left(\begin{pmatrix} 1\\ 0\\ 3 \end{pmatrix}-\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix}\right) & \vec{x} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix} +r\left(\begin{pmatrix} 2\\ 3\\ 4 \end{pmatrix}-\begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}\right) \\\\ \vec{x} &=&\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix}+s\begin{pmatrix} -1\\ 0\\ 1 \end{pmatrix}+t\begin{pmatrix} 0\\ -1\\ 3 \end{pmatrix} & \vec{x} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}+r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix}\\ \hline \end{array} \)

\(\begin{array}{|rcll|} \hline \vec{x} =\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix}+s\begin{pmatrix} -1\\ 0\\ 1 \end{pmatrix}+t\begin{pmatrix} 0\\ -1\\ 3 \end{pmatrix} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}+r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} \\\\ \begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix}+s\begin{pmatrix} -1\\ 0\\ 1 \end{pmatrix}+t\begin{pmatrix} 0\\ -1\\ 3 \end{pmatrix} &=&\begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}+r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} \\\\ s\begin{pmatrix} -1\\ 0\\ 1 \end{pmatrix}+t\begin{pmatrix} 0\\ -1\\ 3 \end{pmatrix} -r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}-\begin{pmatrix} 1\\ 1\\ 0 \end{pmatrix} \\\\ \mathbf{ s\begin{pmatrix} -1\\ 0\\ 1 \end{pmatrix}+t\begin{pmatrix} 0\\ -1\\ 3 \end{pmatrix} -r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} } &=& \mathbf{ \begin{pmatrix} 0\\ 0\\ 2 \end{pmatrix} } \\ \hline \end{array}\)

 

\(\begin{array}{|lrcll|} \hline (1) & -s-r &=& 0 \\ & \mathbf{r} &=& \mathbf{ -s} \\ \hline (2) & -t-2r &=& 0 \\ & t &=& -2r \\ & t &=& -2(-s) \\ & \mathbf{t} &=& \mathbf{2s} \\ \hline (3) & s+3t-2r &=& 2 \\ & s +3(2s)-2(-s) &=& 2 \\ & s+6s+2s &=& 2 \\ & 9s &=& 2 \\ & \mathbf{s} &=& \mathbf{\dfrac{2}{9}} \\\\ & t &=& 2s \\ & t &=& 2\left(\dfrac{2}{9}\right) \\ &\mathbf{t} &=& \mathbf{\dfrac{4}{9}} \\\\ & r &=& -s \\ & r &=& -\left(\dfrac{2}{9}\right)\\ &\mathbf{r} &=& \mathbf{- \dfrac{2}{9} } \\ \hline \end{array}\)

 

\(\mathbf{\vec{P}=\ ?}\)

\(\begin{array}{|rcll|} \hline \vec{x} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}+r\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} \\\\ \vec{P} &=& \begin{pmatrix} 1\\ 1\\ 2 \end{pmatrix}- \dfrac{2}{9}\begin{pmatrix} 1\\ 2\\ 2 \end{pmatrix} \\\\ \vec{P} &=& \begin{pmatrix} 1-\dfrac{2}{9}\\ 1-\dfrac{4}{9}\\ 2-\dfrac{4}{9} \end{pmatrix} \\\\ \mathbf{\vec{P}} &=& \mathbf{\begin{pmatrix} \dfrac{7}{9}\\ \dfrac{5}{9}\\ \dfrac{14}{9} \end{pmatrix} } \\ \hline \end{array} \)

 

laugh

 Aug 5, 2019

11 Online Users